Contribution of cardio-ankle vascular index to prediction of cardiovascular events in the adult urban population: data from the ESSE-RF study (Tomsk) - A. R. Zairova; A. N. Rogoza; E. V. Oshchepkova; E. B. Yarovaya; V. A. Kutsenko; S. A. Shalnova; I. A. Trubacheva; V. S. Kaveshnikov; V. N. Serebryakova; S. A. Boytcov (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To determine the role of cardio-ankle vascular index (CAVI) in predicting cardiovascular events (CVEs) in adult Russian population using model of the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation (ESSE-RF) study (Tomsk).Material and methods. We analyzed the data of 1342 people aged 25-64 (4,3±11,6) years, in whom arterial stiffness was assessed as part of the ESSE-RF study using the vascular screening system VaSeraVS-1500, followed by phone contacts, on average, 4,7 years later. We studied the prognostic role of CAVI in relation to primary composite (cardiovascular death, nonfatal myocardial infarction (MI) or stroke) and secondary composite (all CVEs) endpoints.Results. We revealed that prior myocardial infarction or stroke (n=52) is associated with an increase in CVE incidence from 2,3 to 11,5% (p=0,0003) and from 5% to 23% (p<0,001) for primary and secondary composite endpoints, respectively. In a group of 1290 people (without prior MI or stroke), CAVI was significantly higher in men than in women: 7,4±1,4 vs 7,1±1,3 (p=0,002), despite more young age: 45,4±11,8 vs 48,0±11,3 years (p<0,001). The risk criterion for CVE was CAVI >7,8 (relative risk (RR): 5,06; 95% confidence interval (CI): 2,32-11,06) (p<0,001) and (RR: 3,95; 95% CI: 2,37-6,58) (p<0,001), which retains its predictive value when adjusted for conventional risk factors (RR: 3,13; 95% CI: 1,26-7,75) (p=0,014) and (RR: 2,16; 95% CI: 1,18-3,98) (p=0,013) — primary and secondary composite endpoints, respectively.Conclusion. CAVI has a significant independent value in predicting CVEs in Tomsk adult urban population aged 25-64 years. To clarify the cardiovascular risk, vascular screening with identifying CAVI should be carried out during preventive and screening examinations for men over 35 and women over 45.